2014
DOI: 10.1007/s10393-014-0923-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Rabies Epidemiology in Remote Inuit Communities in Québec, Canada: A “One Health” Approach

Abstract: Rabies is endemic throughout arctic areas including the region of Nunavik, situated north of the 55th parallel of Québec, Canada, and raises public health concerns. The aim of this paper is to provide a descriptive overview of the temporal and regional distributions of three important components of arctic rabies in Nunavik from 1999 to 2012, following a "One Health" approach: animal rabies tests and confirmed cases, dog vaccination, and human consultations for potential rabies exposures. Forty-four cases of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…Luckily, the provision of rabies biologics has been included in the medical insurance settlement, making it available and affordable for residents in China, which is inconsistent with studies reported in less developed countries [10, 29, 30]. In China, basic medical insurance covers most of the cost of rabies vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Luckily, the provision of rabies biologics has been included in the medical insurance settlement, making it available and affordable for residents in China, which is inconsistent with studies reported in less developed countries [10, 29, 30]. In China, basic medical insurance covers most of the cost of rabies vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the fact that dogs are domesticated and taken cared of mostly by women, since they are more likely the ones who stay at home. Additionally, victims of animal bite cases in Quezon Province are more likely above 15 years old (61.41%) which negated other studies which tell otherwise [9,[12][13][14][15][16][17][18][19]. Animal bites occur more frequently in adult since it is usually the adult member in the family who is often associated with handling and caring for the animal.…”
Section: Discussionmentioning
confidence: 97%
“…Supporting the compatibility of the One Health framework for addressing EReNTDs has been its direct application in infectious disease governance and integrated vector prevention and control strategies. This includes successful vector control interventions in Chad, where restricted application of insecticides to cattle leg extremities was used to address HAT, application of the One Health model for coordination and control efforts for rabies and other canine-related zoonoses, and the importance of One Health and the globalized food supply chain (201,272,(339)(340)(341).…”
Section: Application Of the One Health Initiative To Erentdsmentioning
confidence: 99%